2008
DOI: 10.1007/s00384-008-0488-y
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A2 expression, stage, and survival in colorectal cancer

Abstract: HLA-A2 positive patients exhibit poorer tumor differentiation. This might account for a non-significant difference in OAS. The use of HLA-A2 negative patients as control cohort in CRC vaccinations would rather underestimate potential treatment-related survival effects. Therefore, we suggest they constitute a valid auxiliary control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…Our results conflict with the study by Kiewe et al who found no statistically significant difference in 5-year survival and overall survival between HLA-A2-positive and HLA-A2--negative groups of patients with colorectal cancer [2]. One possible explanation for these differences might be differences in the patient cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results conflict with the study by Kiewe et al who found no statistically significant difference in 5-year survival and overall survival between HLA-A2-positive and HLA-A2--negative groups of patients with colorectal cancer [2]. One possible explanation for these differences might be differences in the patient cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…This percentage is slightly higher than the prevalence of HLA-A2 antigens in the Caucasian population in Central and Western Europe, which is around 45% (42.6-51.3%), and also higher than in the results of the study by Kiewe et al who found a frequency of exactly 50% of HLA-A2 expression. [2] However, these findings are not statistically significant.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is noteworthy that in our study the functionality of intratumoral T cells was not analyzed, since this study focused on the HLA-I/APM expression pattern. In contrast to the general dogma, patients with a HLA-I discordant high/low phenotype had a significant better prognosis compared to the HLA-I high phenotype, which is in line with a report in CRC, in which HLA-A2-positive patients had a poorer tumor differentiation [51]. However, most important finding in this context is limited (T1/T2) tumor disease suggesting that the tumor burden might play a key role in the stage dependent immunological control of OSCC.…”
Section: Discussionsupporting
confidence: 89%
“…Here, we has further confirmed the involvement of HLA-A2 in breast cancer as significant higher expression of HLA-A2/A30 and HLA-A2/A31 haplotype as well as HLA-A30 and A31 alleles in breast cancer patients were reported (Table 3). HLA-A2 has been associated with poor disease outcome in breast [18,21], lung [22], ovarian [23], colorectal [24] and gastric cancer [8,25]. HLA-A2 ?…”
Section: Discussionmentioning
confidence: 99%